Development of skills at the preoperational stage; A comparative study on Cognitive development of Urban and rural children - Wajiha Kanwal, Khalid Mehmood, Rashda Perveen (JECCE, 2023)
The main aim of this study was to compare urban and rural school children *on cognitive development at the preoperational stage. The main question for getting the answer was “What was the level of difference among rural and urban school children on language development, egocentrism, understanding of the environment, locus of control, and block building”. Ten teachers teaching class prep to three in rural schools and ten teachers from urban schools and 25 students from each area were conveniently selected for data collection. Interviews and observations were used to collect data regarding cognitive development at the Piagetian preoperational stage. It was found that urban students were better at language development compared to rural school children. Rural school students were more egocentric compared to urban school students, rural school children were unaware of urban environments, but urban students were aware of rural and urban environments. Urban students showed more conservation compared to rural school children and urban students were more skillful in making buildings. From this study, it was concluded that children in urban schools showed better cognitive development. It was recommended that more facilities and expert teachers may be provided to students of rural areas for better cognitive development.